TEOLOGI PELA: Studi Teologi Kontekstual di Negeri Abubu dan Negeri Tengah-Tengah - Yola Permani Lalopua; Rachel Iwamony (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2019)
The aim of this article is to discover theological notions of pela, a Moluccan local culture, especially the Pela relationship between Abubu and Tenga-tenga in the Central Maluku. The researchers will develop the three cultural models by Hessegrave and Rommen (S: (sumber) source, B: (berita) news, P: (penerima) recipient). The three-culture model illustrates that the Bible’s message came in meaningful speeches and ideas for its sources (prophets, apostles and Bible writers) and recipients (listeners and readers) in Hebrew and Greco-Roman cultures. Generally, the news also has been adjusted in wider aspect, so it becomes totally meaningful to the people in the cultures where Christian message is spread out, the church establishes, and the place where cross-cultural messengers are originated. After that examining effort, it turns out that the theological values in the pela relationship such as the mutual assistances, brotherhood-sisterhood, solidarity, respecting religious faith of one another, manifested in mutual happiness in celebrating some religious events. The values in pela relationships can be established both for pela participants and people outside the pela system.